2023
DOI: 10.3389/fpsyt.2023.987093
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, sham-controlled trial of high-definition transcranial direct current stimulation on the right orbital frontal cortex in children and adolescents with attention-deficit hyperactivity disorder

Abstract: ObjectiveThis study aimed to find out the clinical and cognitive effects of high-definition transcranial direct current stimulation (HD-tDCS) on the right orbital frontal cortex (OFC) in the treatment of attention deficit hyperactivity disorder (ADHD).MethodsA total of 56 patients with ADHD were recruited as subjects and completely and randomly divided into the HD-tDCS group and the Sham group. A 1.0 mA anode current was applied to the right OFC. The HD-tDCS group received real stimulation, while the Sham grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…One type of TES that has been studied in ADHD is tDCS, which involves the application of a weak electrical current to the scalp to modulate cortical excitability. Studies using tDCS have reported improved attention and hyperactivity in children with ADHD [100][101][102][103][104][105]. Therefore, several papers focus on the effects of tDCS on ADHD.…”
Section: Tes In Adhdmentioning
confidence: 99%
“…One type of TES that has been studied in ADHD is tDCS, which involves the application of a weak electrical current to the scalp to modulate cortical excitability. Studies using tDCS have reported improved attention and hyperactivity in children with ADHD [100][101][102][103][104][105]. Therefore, several papers focus on the effects of tDCS on ADHD.…”
Section: Tes In Adhdmentioning
confidence: 99%